Profil Penetrasi Sediaan Gel Antioksidan Ekstrak Kayu Manis (Cinnamomum burmanii) dengan Variasi Hydrocolloid sebagai Gelling agent - Siampa, Jainer Pasca; Wiyono, Weny Indayany; Lestari, Utami Sasmita; Lebang, Julianri Sari; Antasionasti, Irma (Jurnal MIPA, 2022)
The exposure of sunlight consisting UV radiation has been reported to be the main cause of skin cancer and contribute about 80% of the incidence of skin damage. In an attempt to overcome this problem, antioxidant agents have been used both orally and topically. Compared to oral administration, topical route has been found to be preferred due to the direct action to the desired site. Amongst topical preparation, gel possesses numerous because it provides a cool and fresh sensation. Here, we developed gel antioxidant containing cinnamon extract as active ingredient. Cinnamon was selected as it has a very strong antioxidant activity. This study aimed to obtain the penetration profile of the antioxidant gel of cinnamon extract prepared from two different hydrocolloid agents. The gels were made using various concentrations of Carbopol 940 and NaCMC. The prepared gels were further characterized for their antioxidant capacities using the DPPH free radical scavenging method and their total phenolic contents using the spectrophotometric method. The formulation possessing the strongest antioxidant capacity was continued for ex vivo penetration study using Franz diffusion cells. The results exhibited that the total phenolic value of the cinnamon extract obtained was 908.38 ± 6.54 mg GAE/g extract. The penetration percentages for the formula with Carbopol and NaCMC bases were 53.310 ± 1.217% and 27.969 ± 1.151%, respectively, and the retention percentages were 28.495 ± 0.031% and 18.356 ± 0.191%, respectively. Based on these findings, we concluded that cinnamon extract could potentially be formulated into antioxidant gel preparations and formulas based on Carbopol showed the best penetration profile.